Pippi Longstocking Goes Aboard [Pipi nastupuje na loď anglicky] / [book 2] - Lindgren, Astrid, 1907-2002 (The World of Astrid Lindgren, 2020)
Loved by millions of children around the world Pippi Longstocking is one of the most popular children's characters of all time. This new edition of the classic Pippi story by Astrid Lindgren, contains brand new black and white artwork by award-winning illustrator Mini Grey, introducing Pippi's adventurous spirit to a whole new generation of readers. In Pippi Goes Aboard, Pippi Longstocking is back and as crazy and as funny as ever! But for Tommy and Annika,the fun might stop all too soon if Pippi agrees to go back to sea with her father.